Criminology and Criminal Justice: Differences in Programs at the Master's Level - Elizabeth Monk-Turner
Our aim in this work is to: (1) determine how distinct the program structure and curriculum content for graduate education in Criminology was compared to Criminal Justice; and (2) evaluate whether the diversity or consistency of the curriculum in either field varied depending of what type of department was offering the degree. Differences in department titles, hours required for the M.A. degree, program descriptions, curriculum content and curriculum content by department type between M.A. programs in Criminology and Criminal Justice were examined. The results suggested there is both consistency and difference in program structure and in curriculum content across the two fields of study.Criminology, Criminal Justice, Curriculum, Program Development